Mandibulofacial Dysostosis associated with congenital factors impacting the oral cavity - Integrative review (Research, Society and Development, 2024)
The present study aimed to analyze the relationships between Mandibulofacial Dysostosis and its impact on the oral cavity through an integrative literature review. For this, a search was conducted in the MEDLINE®, IBECS®, LILACS®, and SciELO® databases, using Health Sciences Descriptors (DeCS) related to Mandibulofacial Dysostosis, genetics, Congenital Disorders, and Syndrome, combined with boolean operators AND and OR. The integrative review contributes to evidence-based practice in the health field. Data collection followed six methodological steps: defining the topic, establishing inclusion/exclusion criteria, collecting information from selected studies, evaluating the methods used, interpreting and discussing the results, and presenting the conclusions. The results indicated a scarcity of articles investigating the relationship between congenital factors and impacts on the oral cavity, highlighting the need for more research to establish correlations in this regard.